2020
DOI: 10.7554/elife.60552
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-EM analysis of PIP2 regulation in mammalian GIRK channels

Abstract: G protein-gated inward rectifier potassium (GIRK) channels are regulated by G proteins and PIP2. Here using cryo-EM single particle analysis we describe the equilibrium ensemble of structures of neuronal GIRK2 as a function of the C8-PIP2 concentration. We find that PIP2 shifts the equilibrium between two distinguishable structures of neuronal GIRK (GIRK2), extended and docked, towards the docked form. In the docked form the cytoplasmic domain, to which Gβγ binds, becomes accessible to the cytoplasmic membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
65
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(78 citation statements)
references
References 44 publications
12
65
1
Order By: Relevance
“…Given the different behavior of the PIP 2 -bound structures in the simulations, we analyzed the structural changes that led to the short-lived wetting and opening transitions at the HBC gate observed in the 6C3O structure. As previously described in structural and functional studies (Fürst et al 2014; Hansen et al 2011; Li et al 2015; Niu et al 2020; Poveda et al 2017), we observed a key structural change in the C-linker, characterized by a PIP 2 -dependent conversion of the loop into a helix. Thus, we monitored changes in the secondary structure of the C-linker over simulation time in both systems, as shown in Figure 3C and 3E, and subplots A, C, E, G of supplementary Figures 2 and 3.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Given the different behavior of the PIP 2 -bound structures in the simulations, we analyzed the structural changes that led to the short-lived wetting and opening transitions at the HBC gate observed in the 6C3O structure. As previously described in structural and functional studies (Fürst et al 2014; Hansen et al 2011; Li et al 2015; Niu et al 2020; Poveda et al 2017), we observed a key structural change in the C-linker, characterized by a PIP 2 -dependent conversion of the loop into a helix. Thus, we monitored changes in the secondary structure of the C-linker over simulation time in both systems, as shown in Figure 3C and 3E, and subplots A, C, E, G of supplementary Figures 2 and 3.…”
Section: Resultssupporting
confidence: 77%
“…Since PIP 2 binding sites are well resolved in Kir2 (Hansen et al 2011; S. J. Lee et al 2016; Zangerl-Plessl et al 2019) and Kir3 channels (Niu et al 2020; Whorton and MacKinnon 2011, 2013), we used this structural information together with functional data to investigate the possible structural basis for K ATP channel regulation by PIP 2 . Specifically, the aim of the present study was to examine PIP 2 -induced gating transitions after unbinding of ATP from the cytoplasmic domain using Molecular Dynamics (MD) simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Ion channels form selective pores for ions to cross the membrane in response to changes in chemical stimulation, mechanical forces or temperature, and play roles in a wide range of physiological processes, including neuronal disorders. These multisubunit proteins respond to signaling lipids, which in some cases can regulate channel opening [ 72 ]. The zebrafish glycine receptor expressed as a homopentamer in insect cells can be solubilized with SMALP 30010 (0.5% w/v ), and purified by metal affinity and size exclusion chromatography for cryo-EM analysis.…”
Section: Cryo-electron Microscopy Of Multisubunit Complexes In Native Nanodiscsmentioning
confidence: 99%
“…Multiple cryo-EM structures of the K ir 3.2 channel illustrate how PIP 2 mediates an interaction between K ir 3.2 and the α-subunit of a G-protein. 89 Using cryo-EM, the study titrated in increasing concentrations of PIP 2 to trap different states of K ir 3.2. Similar to the chicken K ir 2.2 structure, an upward motion of the C-terminal domain by approximately 6 Å is observed when PIP 2 is bound to the channel.…”
Section: The Cryo-em Revolution and Protein-lipid Interactionsmentioning
confidence: 99%